2020
DOI: 10.1002/cbf.3571
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mitochondria‐associated Ca2+ transporters suppression on oocyte activation

Abstract: Oocyte activation deficiency leads to female infertility. [Ca2+]i oscillations are required for mitochondrial energy supplement transition from the resting to the excited state, but the underlying mechanisms are still very little known. Three mitochondrial Ca2+ channels, Mitochondria Calcium Uniporter (MCU), Na+/Ca2+ Exchanger (NCLX) and Voltage‐dependent Ca2+ Channel (VDAC), were deactivated by inhibitors RU360, CGP37157 and Erastin, respectively. Both Erastin and CGP37157 inhibited mitochondrial activity sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Next, we wanted to know which Ca 2+ channels are involved in the maturation of oocytes. We applied various inhibitors of Ca 2+ channels to observe their effects on oocyte maturation as we previously reported (Wang, Li, Li, et al, 2020; Wang, Li, Meng, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we wanted to know which Ca 2+ channels are involved in the maturation of oocytes. We applied various inhibitors of Ca 2+ channels to observe their effects on oocyte maturation as we previously reported (Wang, Li, Li, et al, 2020; Wang, Li, Meng, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…RR is specifically localized to mitochondria (J. Ma, 1993; Tapia & Velasco, 1997), but the specific target is yet unknown. RR was applied to inhibit [Ca 2+ ] i oscillations during oocyte activation in our previous studies (Petr et al, 2005; Wang, Li, Li, et al, 2020). RR is known to interact with a large number of proteins (DeCaen et al, 2013; Dreses‐Werringloer et al, 2013; Z. Ma et al, 2012; Vincent & Duncton, 2011) including MCU (Tufi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, regarding oocyte metabolism, mitochondria are closely related to apoptosis pathways, such as those involving Ca 2+ , cyclic adenosine monophosphate, and ROS ( Tiwari et al, 2015 ; Chiaratti et al, 2018 ). Recently, Feng et al showed that mitochondrial activity played a critically important role in the maintenance of intracellular Ca 2+ ([Ca 2+ ]i) concentration oscillations during oocyte activation via the Na + /Ca 2+ exchanger (NCLX) and voltage-dependent Ca 2+ channel ( Wang et al, 2020 ), which proved the vital role of mitochondrial function in human fertility. Second, Liang et al demonstrated that the accumulation of mtDNA mutations decreased fertility by impairing the NADH/NAD + redox state of oocytes, which could be rescued by nicotinamide mononucleotide treatment ( Yang et al, 2020 ), revealing the controlling metabolic mechanism behind the deleterious effect of age-accumulated mtDNA mutations on fertility.…”
Section: Mtdnas In Human Infertilitymentioning
confidence: 99%
“…Mitochondria are known to be highly dynamic organelles, as described above, that undergo frequent repeat fission and fusion or branching within the cell. The molecular mechanisms of fission and fusion, which induce morphological changes in mitochondria, have been extensively studied, and it has been suggested that reactive oxygen species (ROS) are associated with these morphological changes [ 30 ]. A high fission rate induces mitochondria from tubular shape to granular form, which is known as mitochondrial fragmentation.…”
Section: Does Mitochondrial Uncoupling Cause Fragmentation or Self-fumentioning
confidence: 99%